Reading the visual form of Malaysian comics art / Karna Mustaqim - Mustaqim, Karna (2015)
People nowadays lives in a convergence culture who witnessing how the meeting of old and new media open up new possibilities in the contemporary culture. One of cultivates popular culture in late nineteenth century is the medium of comics. The amusement of comics invited its reader - young or adult - to be immersed into its world. Taking underrated subject matter in popular visual culture such as comics is an intriguing task. While people would agree that cartoons are valuable reflection of society, yet it is an arduous task to take since it was not yet count as a truly significant scholarship. The lack of appreciation made the richness of local comics unseen and as an important contemporary visual culture remains undiscovered. Articulating the expression of contemporary Malaysian comics is not even more a lucid mission. Working pace by pace in this study begins with documenting to perform an initial reading/viewing of all sources and to take notes about the general ways the visually appears contents of four limited established and eligible comics’ magazines at that time being such as Gila Gila, Ujang, Gempak, and G3, which consider to study its visual form and design. Second, researcher used semiotics analysis to generate the visual form categorization. Based on the contents of formal visual structure and semiotics visual analysis, researcher then finally gain insight from the phenomenology of the arts to explicate the findings. It is important yet meaningful to understand the perspectives in studying visual art such as the comics study; that researcher prereflectively involves as the first-person experience.